2000
DOI: 10.1136/gut.47.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Comparable expression of matrix metalloproteinases 1 and 2 in pouchitis and ulcerative colitis

Abstract: (Gut 2000;47:415-422)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 32 publications
5
65
0
2
Order By: Relevance
“…The gelatinases A (MMP-2) and B (MMP-9) have been shown to be highly upregulated in small as well as large intestinal inflammation in mice and men [11][12][13][14][15][16]. We have recently reported that selective blockage of gelatinases by the synthetic compound RO28-2653 was effectively ameliorating acute ileitis [17] and colitis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gelatinases A (MMP-2) and B (MMP-9) have been shown to be highly upregulated in small as well as large intestinal inflammation in mice and men [11][12][13][14][15][16]. We have recently reported that selective blockage of gelatinases by the synthetic compound RO28-2653 was effectively ameliorating acute ileitis [17] and colitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of Th1-type inflammation (e.g. rheumatoid arthritis, atherosclerosis and colitis) [7][8][9][10] as well as in humans with inflammatory bowel diseases (IBDs) such as ulcerative colitis and Crohn's disease [11][12][13][14][15][16], levels of gelatinases A (MMP-2) and B (MMP-9) are increased in inflamed tissue sites.…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition, immunologically mediated cascades that give rise to the release of MMPs seem to play a central role in the pathogenesis of inflammatory bowel diseases. 21 However, while the role of MMPs in Crohn's disease, ulcerative colitis and pouchitis is well established, 16,22,23 less is known about their relevance in CD. By using in situ hybridization, Daum et al 11 were the first to describe the presence of a high number of MMP-1 þ cells in both the subepithelial region and the lamina propria, while MMP-3 þ and TIMP-1 þ cells turned out to be increased only in the subepithelial region of untreated CD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mucosal MMPs in the differentiation of pouchitis was first examined by Stallmach et al [20]: they revealed that MMP-1 and MMP-2 concentrations in the mucosal biopsy samples were increased in pouchitis compared with uninflamed pouches of patients with UC or familial adenomatous polyposis. Strong MMP-9 and MMP-2 activity was detected in the inflamed pouch being reduced after antibiotic treatment in the study of Ulisse et al [21].…”
Section: Discussionmentioning
confidence: 99%